2015
DOI: 10.12659/aot.894954
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Metabolites Acyl-Glucuronide and Glucoside Affect the Occurrence of Infectious Complications and Bone Marrow Dysfunction in Liver Transplant Recipients

Abstract: BACKGROUND Mycophenolic acid (MPA) prodrugs are anti-proliferative immunosuppressive agents commonly used after organ transplantation. Although they are generally well tolerated by patients, adverse effects may occur. It is postulated that MPA metabolites could also contribute to these adverse effects. MATERIAL AND METHODS The objective of this study was the assessment of concentrations of total MPA and its metabolites, phenyl glucuronide (MPAG), acyl glucuronide (AcMPAG) and glucoside (GluMPA), using liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The equations for MPA, MPAG and AcMPAG were y = 6.0395 x + 0.1258, y = 3.0525 x + 0.0559 and y = 4.0896 x + 0.0127, respectively. To our knowledge, in comparison with other published methods that have simultaneously quantified MPA, MPAG, and AcMPAG (Benoit‐Biancamano et al, ; Delavenne et al, ; Figurski et al, ; Iboshi et al, ; Kawanishi et al, ; Klepacki et al, ; Zegarska et al, ; Zhang et al, ), no other assays have obtained better sensitivity for MPA and MPAG. On the other hand, only Figurski et al () reported a lower LLOQ (0.0002 μg/mL) for free AcMPAG concentration in plasma compared with 0.00467 μg/mL obtained in our assay.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The equations for MPA, MPAG and AcMPAG were y = 6.0395 x + 0.1258, y = 3.0525 x + 0.0559 and y = 4.0896 x + 0.0127, respectively. To our knowledge, in comparison with other published methods that have simultaneously quantified MPA, MPAG, and AcMPAG (Benoit‐Biancamano et al, ; Delavenne et al, ; Figurski et al, ; Iboshi et al, ; Kawanishi et al, ; Klepacki et al, ; Zegarska et al, ; Zhang et al, ), no other assays have obtained better sensitivity for MPA and MPAG. On the other hand, only Figurski et al () reported a lower LLOQ (0.0002 μg/mL) for free AcMPAG concentration in plasma compared with 0.00467 μg/mL obtained in our assay.…”
Section: Resultsmentioning
confidence: 75%
“…We have developed a sensitive LC–MS/MS assay for the simultaneous quantification of MPA, MPAG and AcMPAG in HepaRG cell culture medium, using MPA‐d 3 and MPAG‐d 3 as internal standards. LC–MS/MS assays for MPA and/or metabolites have been described in human plasma (Delavenne, Juthier, Pons, Mariat, & Basset, ; Figurski, Korecka, Fields, Waligorska, & Shaw, ; Kawanishi et al, ; Zegarska et al, ; Zhang, Chow, & Renbarger, ), urine (Benoit‐Biancamano et al, ; Klepacki et al, ), dried blood spots (Iboshi et al, ) and human liver microsomes (Mohamed, Harvey, & Frye, ). In contrast to other biological fluids (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have studied the metabolite AcMPAG as a potential mediator of adverse side effects for patients prescribed MMF both in vitro and in vivo and suggest there may be a relationship between AcMPAG and gastrointestinal side effects; however, AcMPAG has not been convincingly shown to be a mediator of leukopenia. In a study by van Agteren et al, they did not find a difference in AcMPAG concentrations in 332 kidney transplant patients that experienced leukopenia compared to those that did not .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zegarska et al have been reported that AcMPAG concentrations in liver transplant recipients is related to the development of bacterial infection (8). In addition, Yoshimura et al have been reported that the cutoff values of AcMPAG AUC0-24 for successful gastrointestinal acute graft-versushost disease prevention in hematopoietic stem cell transplant patients were 15.6 μg•hr/mL (9).…”
Section: Introductionmentioning
confidence: 99%